Water resources sustainability model for wetland conservation based on anonymous expert elicitation. (February 2021) - Canto-Perello, Julian; Benitez-Navio, Alberto; Martin-Utrillas, Manuel; Martinez-Leon, Jesus; Curiel-Esparza, Jorge
Abstract: Wetlands play a key role in preserving biodiversity and preventing climate change. Their conservation poses an important and pressing challenge. In the Mediterranean region, one of the key threats to wetland survival is the lack of water due to competition for resources. The selection of the most sustainable water resources for wetland conservation is a complex elicitation problem. A novel Water Resources Sustainability Model (WRSM) focused on water quality has been developed to support the decision-making. This collaborative elicitation model is based on the analytical hierarchy process and uses the reference environmental status of the wetland. The model can be used to discriminate which water resources are more sustainable for the conservation of the wetland. The WRSM has been applied successfully to Las Tablas de Daimiel National Park. The framework enables establishing priorities when analyzing in terms of water quality any surface, recycled or underground water resources. Highlights: Elicitation model contributing to the sustainable allocation of water resources. Model rates water resources under nine quality physico-chemical indicators. Systematic method of collaborative elicitation based on analytical hierarchy process. Traceability and transparency in achieving consensus among the panelists. Prioritizing surface, recycled or underground resources based on water quality.